A systematic multi-technique comparison of luminescence characteristics of two reference quartz samples - Schmidt, Christoph; Chruścińska, Alicja; Fasoli, Mauro; Biernacka, Magdalena; Kreutzer, Sebastian; Polymeris, Georgios S.; Sanderson, David C. W.; Cresswell, Alan; Adamiec, Grzegorz; Martini, Marco (Journal of luminescence, 2022)
Further developments in luminescence dating, dosimetry and temperature-sensing require a deep understanding of luminescence processes and their driving parameters. Natural quartz is one of the most widely used minerals for these purposes. Still, poor reproducibility of results often hampers comparability and credibility from findings in the literature. We identified the lack of suitable natural reference samples as a pivotal problem impeding significant progression. Ideally, basic investigations involve several laboratories working on well-characterised reference quartz samples with different characteristics. Investigations should include multiple complementing methods to analyse luminescence properties and mineralogical and geochemical composition. Here, we present such a multi-technique luminescence comparison of two natural quartz samples. Next to the recently introduced Fontainebleau (FB) reference quartz, we propose another reference sample derived from the ‘Silver Sands of Morar’ (lab code ‘MR’; Scotland, UK). Our experiments confirm that both quartz samples behave fundamentally different in terms of signal composition and sensitivity. The comparative characterisation of both samples targeted electron traps via thermoluminescence (TL) and optically stimulated luminescence (OSL) techniques and luminescence centres via radioluminescence and time-resolved OSL spectrometry. In summary, we conclude that all observed differences are likely the results of divergent defect concentrations rather than variances in defects' composition (nature). The measurement data of our study are accessible open-access for inspection by others.
Gesehen am 07.02.2023